Early Follicular Phase Human Chorionic Gonadotropin Addition May Improve the Outcomes of In Vitro Fertilization/Intracytoplasmic Sperm Injection in Patients With “Unpredictable” Poor Response to Gonadotropin-Releasing Hormone Antagonist Protocol - Chunhui Zhang; Fangrong Wu; Zexuan Wu; Bolan Sun; Cheng Chen; Weiping Qian (Frontiers in Endocrinology, 2021)
PurposeTo compare the effects of early and mid-late follicular phase administration of 150 IU of human chorionic gonadotropin (hCG) on gonadotropin-releasing hormone (GnRH) antagonist protocol in “unpredictable” poor ovarian response (POR) women undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment.MethodsA retrospective single-center cohort study was conducted on 67 patients with “unpredictable” POR in their first IVF/ICSI cycle receiving GnRH antagonist protocol. Patients were treated with a second IVF/ICSI cycle using the same GnRH antagonist protocol with the same starting dose of recombinant follicle-stimulating hormone (rFSH) as the first cycle; a daily dose of 150 IU of hCG was administrated on either stimulation day 1 (Group A, n = 35) or day 6 (Group B, n = 32). The number of oocytes retrieved, number of usable embryos, serum level of estradiol (E2) on day of hCG trigger, and clinical pregnant outcomes were studied.ResultsThe addition of 150 IU of hCG on either the first day or sixth day of stimulation increases the serum level of E2, luteinizing hormone (LH), and hCG on the day of hCG trigger. Only the use of 150 IU of hCG on the first stimulation day improved the number of oocytes retrieved, mature of oocytes, and usable embryos, but not the addition of hCG on stimulation day 6. Implantation rate, clinical pregnancy rate, and ongoing pregnancy rate showed an increasing trend in patients receiving 150 IU of hCG in the early phase compared with mid-late phase, even thought there was no statistically significant difference.ConclusionsOur study demonstrated that adding 150 IU of hCG in subsequent GnRH antagonist cycle in “unpredictable” poor responders is associated with the improvement of response to stimulation. Furthermore, early follicular phase addition of 150 IU of hCG significantly increased the number of oocytes retrieved and usable embryos than did the mid-late addition of the same dose.